From Physical Activity Intention to Behavior: The Moderation Role of Mental Toughness Among College Students and Wage Earners - Cao, Zhenfeng; Yang, Yongtao; Ding, Weiwei; Huang, Zhijian (Frontiers in Psychology, 2021)
This study explored the correlation between mental toughness and physical activity, and the moderation role between physical activity intention and subsequent behavior among college students and wage earners. 591 college students (251 male, 340 female) aged from 19 to 24 and 285 (157 male, 127 female) wage earners aged from 27 to 58 recruited from seven colleges and five cities in China. A theory of planned behavior questionnaire, mental toughness inventory, and the international physical activity questionnaire was completed online. Results showed that attitudes, subjective norms, and perceived behavioral control explained 46.5% and 38.3% substantial variance in physical activity intention among college students and wage earners separately. Intention predicted physical activity behavior significantly among college students and wage earners. Structural equation modeling indicated that the TPB model and the moderation model have an adequate to good fit except the TPB model among wage earners. Mental toughness was positively correlated with physical activity among college students and wage earners, and had a significant moderation role in intention-behavior gap among college students, and partially affected the transfer of physical activity intention to behavior among college students. Individuals with high mental toughness had high levels of physical activity regardless of intention, while physical activity of low mental toughness was low and unstable. Future research should further explore the correlation between intention and physical activity and the moderation role of MT in different populations used longitudinal study in order to better understand the correlation between intention and physical activity, and the transition from intention to physical activity and to be better guidance physical activity intervention to promote physical activity.